“When you provide abortion services, you are looked upon as a bad guy”: experiences of abortion stigma by health providers in Nigeria - Friday Okonofua; Lorretta Ntoimo; Louise Bury; Suzanna Bright; Lesley Hoggart (Global Health Action)
Background Abortion stigma as reported globally has been inadequately documented empirically in Nigeria, Africa’s most populous country with a restrictive abortion law and a high rate of unsafe abortions. Objective The objectives of this study were to investigate the ways in which abortion stigma is experienced by Nigerian health professionals and how such experiences influence health professionals’ practice of safe abortion and post-abortion care. Methods The study utilized qualitative research consisting of in-depth interviews with 10 abortion providers. We elicited information with an open-ended interview guide that investigated the understanding of participants’ experiences of abortion stigma in Nigeria. The data were analysed qualitatively and thematically using Atlas.ti. Results The themes centred on perceptions and experiences of stigma among the providers interviewed. Participants’ experiences of abortion stigma included the following: being treated differently to other health professionals; experiencing disapproval and disrespect; name-calling and societal judgement; tagging and profiling of clinics by anti-abortionists; and social isolation. Participants attributed stigma to cultural and religious beliefs, the restrictive national abortion law, and pointed to hypocrisy. Some reported effects of stigma on providers included a feeling of insecurity, social exclusion, secrecy, and insincerity in clinical practice, discouragement, and guilt feelings. Despite the negative impacts, many respondents reported a sense of satisfaction stemming from their views that they were saving lives. Conclusion Systematic efforts to address these adverse factors could reduce the level of stigma experienced by providers, with a potential follow-through effect of improving women’s access to safe abortion care in Nigeria.